Prior fear conditioning and reward learning interact in fear and reward networks - Bulganin, Lisa; Bach, Dominik R.; Wittmann, Bianca C. (Frontiers in Behavioral Neuroscience, 2014)
The ability to flexibly adapt responses to changes in the environment is important for survival. Previous research in humans separately examined the mechanisms underlying acquisition and extinction of aversive and appetitive conditioned responses. It is yet unclear how aversive and appetitive learning interact on a neural level during counterconditioning in humans. This functional magnetic resonance imaging (fMRI) study investigated the interaction of fear conditioning and subsequent reward learning. In the first phase (fear acquisition), images predicted aversive electric shocks or no aversive outcome. In the second phase (counterconditioning), half of the CS+ and CS- were associated with monetary reward in the absence of electric stimulation. The third phase initiated reinstatement of fear through presentation of electric shocks, followed by CS presentation in the absence of shock or reward. Results indicate that participants were impaired at learning the reward contingencies for stimuli previously associated with shock. In the counterconditioning phase, prior fear association interacted with reward representation in the amygdala, where activation was decreased for rewarded compared to unrewarded CS- trials, while there was no reward-related difference in CS+ trials. In the reinstatement phase, an interaction of previous fear association and previous reward status was observed in a reward network consisting of substantia nigra / ventral tegmental area (SN/VTA), striatum and orbitofrontal cortex (OFC), where activation was increased by previous reward association only for CS- but not for CS+ trials. These findings suggest that during counterconditioning, prior fear conditioning interferes with reward learning, subsequently leading to lower activation of the reward network.